Risk of Amiodarone-Induced Pulmonary Toxicity Versus Placebo in Patients with Cardiac Arrhythmias and Heart Failure: A Meta-Analysis of Randomised Controlled Trials - Dzaki Murtadho; Dewi Wahyu Fitrina; Deddy Herman (HM Publisher, 2026)
Background: Amiodarone is the most effective antiarrhythmic agent for maintaining sinus rhythm, yet its long-term use is constrained by extracardiac toxicity, of which pulmonary toxicity is the most feared because it carries appreciable mortality and is frequently misdiagnosed. No contemporary meta-analysis has isolated amiodarone-induced pulmonary toxicity as the single primary endpoint across cardiac arrhythmia and heart-failure populations; this study quantified that risk. Methods: PubMed/MEDLINE, Scopus and Web of Science were searched for placebo- or usual-care-controlled randomised controlled trials (RCTs) of oral amiodarone in adults with cardiac arrhythmia or heart-failure indications reporting pulmonary toxicity. Two reviewers extracted 2×2 data and assessed risk of bias with Cochrane RoB 2.0. Because the outcome was dichotomous, the risk ratio (RR) was pooled using a DerSimonian–Laird random-effects model, with the odds ratio (OR) and Peto OR as corroborative measures. Results: Nine RCTs comprising 6,209 patients (3,175 amiodarone; 3,034 control) were included. Pulmonary toxicity occurred in 77 of 3,175 amiodarone-treated patients (2.43%) versus 42 of 3,034 controls (1.38%). Amiodarone significantly increased pulmonary-toxicity risk (RR 1.70, 95% CI 1.17–2.45, p = 0.005), with no detectable heterogeneity (I² = 0%). The OR (1.74) and Peto OR (1.81) were concordant, and the estimate remained harmful under every single-study deletion (RR 1.46–2.64). Higher-dose strata showed a numerically larger effect (RR 2.50) than lower-dose strata (RR 1.69; subgroup p = 0.48). Conclusion: Amiodarone was associated with an approximately 70% relative increase in pulmonary-toxicity risk versus placebo, a robust and homogeneous finding. The absolute excess was modest (about one additional case per 95 patients treated), supporting continued use with structured baseline and periodic pulmonary surveillance, particularly at higher maintenance doses and longer durations.